A study on morbidity and nutritional status of deaf-mute children attending a special school of Hyderabad, Telangana - Snehika, Allampally; Koteswaramma, C. H.; Kumar, M. Vijay; Madhuri, V. (International Journal Of Community Medicine And Public Health, 2023)
Background: Hearing is necessary for the development of language, speech, and cognitive skills. Hearing loss effects a child’s ability to learn, communicate, and to socialize. Hearing impairment often goes unnoticed which compromises a child’s ability to speak and express their needs. If no rehabilitation is done child develops physical and mental issues. Deaf-mute children are neglected in these aspects hence present study aimed to assess their nutritional and morbidity status among them. The objective of this study was to assess the morbidity profile among Deaf mute children attending organizations in Hyderabad and to determine their nutritional status among them. Methods: A cross-sectional study was conducted over for 2 months during May and June 2022 among 50 deaf-mute children attending a special school in Hyderabad. A pre-designed semi-structured questionnaire was used to interview subjects after taking permission from the principal and confidentiality was ensured. The collected data were analysed using MS Excel and Epi-Info software. Results: The mean age was 13.4 years with the majority being female children (82%). The prevalence of undernutrition was 16% and the prevalence of overnutrition was 26%. The prevalence of undernutrition was more among boys and the prevalence of overnutrition was slightly more among girls. The morbidity pattern showed that 24 (47.5%) suffered from any disease during the past 3 months with the commonest morbidity being dental caries (74%). Conclusions: The study showed a high proportion of deaf-mute children developing nutritional deficiencies and morbidities; hence an effective collaboration and coordination between these organizations and ICDS anganwadi centres are needed for the improvement of nutritional status.